Windows 8 for dummies - Rathbone, Andy (Hoboken, N.J John Wiley & Sons, 2012)
The bestselling tech book of all time is now updated for Windows 8 Microsoft Windows, the operating system that runs nearly 90 percent of the world's computers. Windows 8 will offer new interface updates, cloud-based services, and much more
Windows 8 stuff everybody thinks you already know: What is Windows 8? ; The mysterious new start screen ; The traditional desktop ; Basic desktop window mechanics ; Storage : internal, external, and in the sky -- Working with programs, apps, and files: Playing with programs, apps, and documents ; Finding the lost ; Printing your work -- Getting things done on the Internet: Cruising the Web ; Being social : mail, people, calendar, and messaging ; Safe computing -- Customizing and upgrading Windows 8: Customizing Windows 8 with the control panel ; Keeping Windows from breaking ; Sharing one computer with several people ; Connecting computers with a network -- Music, photos, and movies: Playing and copying music in Media Player ; Fiddling with photos (and movies) -- Help!: The case of the broken window ; Strange messages : what you did does not compute ; Moving from an old PC to a new Windows 8 PC ; Help on the Windows 8 help system -- The part of tens: Ten things you'll hate about Windows 8 (and how to fix them) ; Ten or so tips for touchscreen owners
"Learn to: use the start screen to launch apps; send e-mail and link to social media accounts; create music playlists, watch videos, and organize photos; troubleshoot common problems"--Cover
Includes index
13
Keywords: Microsoft Windows (Computer file); Operating systems (Computers)